-35=-4(5p+5)+5(3p-1)

Simple and best practice solution for -35=-4(5p+5)+5(3p-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -35=-4(5p+5)+5(3p-1) equation:



-35=-4(5p+5)+5(3p-1)
We move all terms to the left:
-35-(-4(5p+5)+5(3p-1))=0
We calculate terms in parentheses: -(-4(5p+5)+5(3p-1)), so:
-4(5p+5)+5(3p-1)
We multiply parentheses
-20p+15p-20-5
We add all the numbers together, and all the variables
-5p-25
Back to the equation:
-(-5p-25)
We get rid of parentheses
5p+25-35=0
We add all the numbers together, and all the variables
5p-10=0
We move all terms containing p to the left, all other terms to the right
5p=10
p=10/5
p=2

See similar equations:

| (X+8)(x+2)=96 | | -9y-2=52 | | 50x-128=-472 | | 32=a | | 30y-10-y-8y=33 | | 33+5y-10=17y-9-4y | | 2(3^x+3^(x+1))=45 | | 5x+5^x+1-30=0 | | 14c+4c-8c-4c=18 | | 2x+3•(-3x/2+73)=134 | | 7+-3/5b=14 | | 6×x×3=90 | | 5x–20=75 | | 3.2+2k=8.2-4 | | 5x–20=75 | | 4e^2+26=170 | | 16. 5x–20=75 | | 2x+3(-3x/2+73)=134 | | 2(x-15)=16 | | 4^2t=3^t-1 | | x+0.8=1.6 | | 168=-­‐8x | | 6.8=z+22 | | h+1/2=16 | | 4.2r=16.8 | | 3(x-4)-2(3x+4)=4(3x)+5x+4 | | 4*l−7/3=19 | | 6x-15-2x-2-4x-7=180 | | 3/6=4/y | | 2/4=3/y | | 22=10+(0.05*m) | | 2b-3=81 |

Equations solver categories